Pembuatan Salinan Akta Berdasarkan Protokol Notaris Werda Yang Telah Diserahkan Pada Notaris Pemegang Protokol - Lentra Nugraha (Lex Renaissance, 2020)
The problems raised in this research are: First, what are the legal consequences for the switched protocol holder being able to make a copy pf deed based on the minutes that have been submitted? Second, how is the protocol for the retired notary make a copy of deed of the minute? This legal research is a combination of normative and empirical study, which uses a statutory and case-based approach and qualitative analysis methods. The results of this study conclude that the legal consequence for switching protocol holders is that they can make a copy of deed based on the minute that has been submitted. As for a damaged certificate, a copy cannot be made again, whereas if the certificate is in good condition then a copy can be made based on its contents. It is the notary who holds the minute of the deed (the recipient of the protocol from the retired notary) who can make the copy, and if the minute is damaged due to negligence then the notary must be responsible, including the one who submitted the protocol (the retired notary). Furthermore, the Notary protocol from another Notary which at the time of submission is 25 years old or more must also be submitted by the Notary who receives the protocol to the Regional Supervisory Council.